Rights of third parties in insurance law in Malaysia / Chan Wai Meng - Chan, Wai Meng (2007)
An insurance policy can be used as an instrument to confer benefits to, or to protect, a person who is not a party to the policy. However, at common law, the rights of the third party are hampered by the doctrine of privity and the strict requirement for compliance of the policy terms. To address these issues, the legislature bas enacted provisions to confer rights on selected third parties in selected types of insurance policies. This thesis studies and analyses the rights of third parties in insurance law in Malaysia, particularly the rights conferred by the legislature. Chapters 2 to 4 examine the rights conferred on selected classes of third parties, first, a person who is nominated by the policy owner to receive the policy moneys upon the happening of the insured event; secondly, the assignee of the policy or its proceeds; and thirdly, the beneficiary of a statutory trust. Chapter 5 analyses the rights of third parties in motor insurance, namely, a person who is injured in a motor accident, the hospital that treats him and an authorised driver. Chapter 6 deals with the rights of third parties in a group policy. This thesis aims to demonstrate that there are many shortcomings in the current laws. Some of the statutory provisions are out-dated. In certain situations, the legislature has eroded the third party rights through the enactment of statutes and the amendment to the existing statutory provisions. There are also instances where a third party claimant is not adequately protected even though there is a compulsory insurance scheme which was established with the intention of protecting him. This thesis will conclude with recommendations for legislative reform to address the shortcomings in the existing laws pertaining to the rights of third parties in insurance law in Malaysia.